Decorin concentrations in canine normal and neoplastic mammary gland tissues. Issue 10 (17th August 2020) - Szczubiał, Marek; Kankofer, Marta; Wawrzykowski, Jacek; Dąbrowski, Roman; Łopuszyński, Wojciech; Bochniarz, Mariola; Brodzki, Piotr
Abstract: In the present study, the concentration of decorin in canine normal and neoplastic mammary gland tissues was examined to understand the potential role of decorin in development and progression of canine mammary tumours. The homogenates of 48 mammary gland tumours (10 benign and 38 malignant) and 10 samples of normal canine mammary gland tissue were used in the study. The presence and quantification of decorin was examined in the homogenates using Western blot and specific canine ELISA. Western blotting confirmed the presence of decorin both in the normal mammary gland tissues and in the mammary gland tumours. The concentration of decorin was significantly higher ( p  < .05) in the benign tumours and non‐metastatic malignant tumours than in the normal mammary gland. The concentration of decorin was significantly lower ( p  < .05) in the malignant tumours with metastasis to regional lymph nodes compared with benign tumours and non‐metastatic malignant tumours. No significant differences were found in the level of decorin between the benign and the non‐metastatic malignant tumours. Both the histological type of malignant tumours and the histological grade did not significantly affect the concentration of decorin. These findings suggest that neoplastic transformation in the canine mammary gland leads to increase in the decorin protein synthesis. The reducing decorin concentration in canine malignant mammary tumours appears to facilitate the metastatic spread of these tumours.